Representation of cloud ecosystem using engineering methodologies (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
Cloud Computing has fascinated massive consideration for business in spite of lot of technologies and business models in the market. The operational particulars within the cloud are not coherent enough to customers. Hence, this paper provides the method to derive trusted cloud computing scaffold. This scaffold is represented using the engineering methodologies. In this work we use elementary engineering principles of computation to represent the cloud eco-system, comprising of complete cloud system from the end-user perspective.